KAJIAN PENGARUH JENIS MATERIAL TERHADAP KUALITAS UKURAN PADA PROSES PENEKUKAN PELAT DENGAN METODA ANOVA - Rosidi Rachman; Almahdi Almahdi; Darius Yuhas (Jurnal Poli-Teknologi, 2021)
Abstract In previous research, it has been proven that the measurement technique, setting and use of quality measuring instruments can increase the quality of measurements during the bending process of steel plates (ST.37). However, this research has not examined the types of materials other than steel, even though other materials apart from ST.37, for example aluminum plates, brass plates and steel plates are widely used, especially in the manufacturing industry.. Therefore, the aim of this research is to analyze the effect of the type of material on the quality of the measurement in the bending process. This study uses an experimental method, combined with a theory that supports the discussion of the problem. The materials used are 3 different types of material plates (aluminum plate, brass plate and steel plate). The parameters observed include the measurement technique, setting and use of measuring instruments. Each material received 10 repetitions of the measurements. These three parameters were analyzed using ANOVA statistics, in order to determine the quality of the measurement of each material and the most dominant factors affecting the quality of the measurements. Keywords: Plates, measurements, bending processes, and statistics.